Employment of relationship marketing strategies for enhancing customer satisfaction in Malaysian private hospitals - Lau, C. C.; Ahmad, M. I. (Academy of Marketing Science, 1997)
Marketers, in academia and business practice, are continually searching for new and more effective methods. One such approach that has gained popularity in Malaysian private hospitals, in recent years, is relationship marketing. This study examined the extent to which relationship marketing strategies are used to improve customer satisfaction and maintain customer loyalty. The study results indicate that a good relationship marketing strategy can be crucial for private hospitals to gain a competitive edge, especially with the rapid development of private hospitals in the urban centres.